2021
DOI: 10.3389/fnins.2021.764520
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Odor Hedonic Perception: An Overview

Abstract: Odor hedonic evaluation (pleasant/unpleasant) is considered as the first and one of the most prominent dimension in odor perception. While sex differences in human olfaction have been extensively explored, gender effect in hedonic perception appears to be less considered. However, a number of studies have included comparisons between men and women, using different types of measurements (psychophysical, psychophysiological,…). This overview presents experimental works with non-specific and body odors separately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 111 publications
(119 reference statements)
1
12
0
Order By: Relevance
“…Indeed, no difference in IDTs and OHRs was observed between men and women, knowing that the sex ratio was unbalanced in the sample. Because of the well-established sex differences in human odor sensitivity and odor hedonic perception 18 , 57 , this effect could be thoroughly examined in future research with a larger sample composed of a homogenous number of men and women. Likewise, no significant difference in hunger level was found between each odor session and participants hunger level had no influence on detection thresholds and OHRs at detection threshold and pure solution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, no difference in IDTs and OHRs was observed between men and women, knowing that the sex ratio was unbalanced in the sample. Because of the well-established sex differences in human odor sensitivity and odor hedonic perception 18 , 57 , this effect could be thoroughly examined in future research with a larger sample composed of a homogenous number of men and women. Likewise, no significant difference in hunger level was found between each odor session and participants hunger level had no influence on detection thresholds and OHRs at detection threshold and pure solution.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, several studies showed a great flexibility of odor hedonic perception. Thus, differences were observed in relation to individual characteristics such as age 10 12 , sex 13 18 , the experience towards odorants 19 and physiological state 20 , 21 , diseases such as depressive disorders 22 , schizophrenia 23 , 24 or Parkinson’s disease 25 , 26 and recently with SARS-CoV-2 27 . Odor hedonic perception also appeared to depend on repeated exposures 28 , 29 , verbal influence 30 , 31 , or stimulus presentation pathway (orthonasal vs. retronasal) 32 .…”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is not consistent across other studies 39,40 ; however, the predominant view is that women have a greater pain responsiveness for most pain modalities 41 . This is not unique to pain, as there is evidence that women are often more perceptive across multiple sensory domains 23 , exhibiting a greater detection and discrimination sensitivity to tactile 42 , olfactory 43 , and visual stimuli 44 . Our results are also in line with the clinical reality which has shown that gender differences exists with respect to pain tolerance and thresholds, and that there is a higher prevalence of chronic pain conditions for females 41,45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…This is not unique only to pain, as there is evidence that women are often more perceptive than men across multiple sensory domains (Hashmi and Davis, 2014). Women were shown to have a greater detection and discrimination sensitivity than men to tactile (Boles and Givens, 2011), olfactory (Bontempi et al, 2021), and visual stimuli (Shaqiri et al, 2018). Our results are also in line with the clinical reality which has shown that gender differences exists with respect to pain tolerance and thresholds, and that there is a higher prevalence of chronic pain conditions for females (Meints et al, 2018; Sorge and Totsch, 2017; Templeton, 2020).…”
Section: Discussionmentioning
confidence: 99%